1631. Mycobacterium septicum: A 6-year Clinical Experience from a Tertiary Hospital and Reference Laboratory. (31st December 2020) - Go, John Raymond U; Campioli, Cristina G Corsini; Saleh, Omar Abu; Wilson, John; Deml, Sharon; Wengenack, Nancy
Abstract: Background: Mycobacterium septicum is a rapidly growing non-tuberculous mycobacterium. It is a ubiquitous organism capable of causing infections in both healthy and immunocompromised individuals. Only a few cases have been reported to date, and standard therapeutic regimens, and optimal treatment duration have not been defined. Methods: We conducted a retrospective chart review of all patients seen at Mayo Clinic in Rochester, MN from July 2014 to March 2020 from whom Mycobacterium septicum was isolated in culture by our clinical microbiology laboratory. Results: There were 12 patients identified with M. septicum infection – 7 males and 5 females. The average age was 67 years, with an age range of 48 to 80 years. Seven of 12 isolates obtained were from sputum samples. Only one patient was on immunosuppressive medication. Three cases were considered clinically significant infections for which directed anti-mycobacterial therapy was instituted. In two of these three cases, co-infection with Mycobacterium avium complex (MAC) was seen. Underlying structural lung disease was present in the two cases of pulmonary infections. Peritoneal dialysis catheter-related peritonitis was seen in the third case. All the isolates were susceptible to amikacin, ciprofloxacin, imipenem, linezolid, moxifloxacin, and trimethoprim-sulfamethoxazole (TMP-SMX). The isolates were resistant to clarithromycin and doxycycline. Patient Characteristics, Associated M. septicum Illness, and Therapy Provided Antimicrobial Susceptibility Profiles of the Mycobacterium septicum Isolates, MIC (mcg/mL) and Interpretation Patient Demographics and Specimen Source of Mycobacerium septicum Isolates Conclusion: M. septicum is an unusual cause of non-tuberculous mycobacterial infection. The presence of a foreign body may increase the risk of infection. Individuals with underlying structural lung disease are also likely to be at increased risk of developing pulmonary infection. Generalized treatment recommendations are limited by the lack of prospective controlled trials; hence, optimal antibiotic regimen and treatment duration have not been firmly established. Susceptibility testing should be performed to guide treatment selection, but the use of combination therapy with potentially empiric agents like amikacin, ciprofloxacin, imipenem, linezolid, moxifloxacin, and TMP-SMX as demonstrated in this small study, can be considered. A high rate of macrolide resistance was noted in our study. Disclosures: All Authors : No reported disclosures